A Comic-Based Learning Approach Grounded in Islamic Constructivism: Utilizing Canva to Explore Solar System Concepts - Wiliyanti, Vandan; Yuberti, Yuberti; Ramadhani, Evi Nur (Jurnal Penelitian Pembelajaran Fisika, 2024)
The purpose of this research endeavor is to evaluate the feasibility of comic-based educational media grounded in an Islamic nuanced constructivist framework, employing Canva applications for the instruction of solar system content. The study was carried out in accordance with Thiagarajan's 4D model, engaging seventh-grade students from SMP/MTs. Data were gathered from the feedback of both students and educators, in conjunction with validation from subject matter specialists, media professionals, and religious authorities. The outcomes of the investigation reveal that the material validation from experts achieved a score of 91%, media experts assigned a score of 86%, while religious authorities contributed a score of 82%. These findings signify a commendable degree of validation. In summary, drawing upon the assessments from experts and the affirmative feedback from educators and students, it can be inferred that the comic-based learning media, rooted in an Islamic constructivist paradigm utilizing Canva applications, serves as an efficacious and stimulating educational instrument for imparting knowledge regarding solar system concepts.